Atypical Presentation of Wilson’s Disease - Gurubacharya, SM; Gurubacharya, RL (Journal of Nepal Paediatric Society, 2008)
Key words: Wilson's disease (WD); KF ring; Hyperpigmentation; Vitamin A deficiency DOI = 10.3126/jnps.v28i2.1390 J. Nepal Paediatr. Soc. Vol.28(2) 2008 p.66-67